The use of a psychiatric overflow unit in a large urban community hospital to improve process outcomes - Bahareh Aslani-Amoli; Alex Marwaha; Maria Stepanova; Sarah Rhine; Samir Nader; Linda Henry; John Howell; Tanveer Gaibi (JEM Reports)
Background: The United States is experiencing a mental health (MH) crisis with limited resources to meet demands. We established a 5-bed psychiatric overflow unit (POU) within the emergency department (ED) as a care alternative. Objective: Determine the clinical utility and safety of a POU in care delivery to patients in a MH crisis compared to the main ED (controls). Methods: Retrospective study using data from electronic health record/chart review [October 1, 2021–May 31, 2022 (POU established January 2022)] for all ED patients ≥12 years admitted with MH crisis. Per triage nurse, patients for potential hospital admission were POU admitted when medically cleared. Clinical utility definition: ED length of stay (LOS); patient safety definition: return to ED within 72 ​h for same complaint. Results: Patients (n ​= ​919; POU ​= ​302, main ED ​= ​617) were 61.4% male, mean age 39.7 ​± ​15.6 years, 84.2% ESI 2, 61.7% admitted/transferred, average ED LOS was 932.3 ​± ​804.7 ​min and no returns within 72 ​h. POU had longer ED LOS (1058.7 ​± ​736.5 vs 884.6 ​± ​824.6, P ​< ​0.0001) but no differences among admitted/transferred patients comparing POU vs controls (P ​> ​0.05); Among discharged patients POU compared to main ED had a longer mean ED LOS (819.9 ​± ​779.8 vs 486.4 ​± ​577.3, P ​< ​0.0001); Removal of police escort patients did not change POU ED LOS (P ​< ​0.05). Conclusions: An ED POU, staffed with behavioral health nurses, had equivocal safety and clinical utility as the main ED potentially providing an alternative care-delivery option when ED space and MH resources are limited.